Ankle bracing's effects during a modified agility task: analysis of sEMG, impulse, and time to complete using a crossover, repeated measures design. - Henderson, Zachariah J.; Sanzo, Paolo; Zerpa, Carlos; Kivi, Derek (Sports Biomechanics, 2023)
This study explored the effects of no braces, softshell (AE), and semi-rigid (T1) ankle braces on time to complete a modified agility task, as well as lower extremity muscle activity and impulse during the change of direction component of the task. Thirty-nine healthy, active individuals completed a modified agility task under the three brace conditions. Time to complete the modified agility task, along with mean surface electromyographic activity (sEMG) and impulse during the deceleration and propulsive phases of the task were measured. There were no significant differences across conditions with respect to sEMG or impulse measures during the deceleration or propulsive phases. There was a significant change in time to complete the modified agility task, F(2,76) = 17.242, p< 0.001, ηp2 = 0.312. Post-hoc analysis revealed a significant increase in time to complete the modified agility task when wearing the AE (0.16 (95% CI, 0.062 to 0.265) seconds, p< 0.001) and T1 (0.20 (95% CI, 0.113 to 0.286) seconds, p< 0.001) ankle braces compared to no braces. It appears that performance on a modified agility task may be diminished when wearing ankle braces, although sEMG activity and impulse are unaffected.